The Relationship of Physical Activities and Student Learning Outcomes of Physical Education - Tri Irianto; Ramadhan Arifin; Muhammad Firmansyah (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to determine the relationship between physical activity and learning outcomes of sports physical education and the health of students at SMA Negeri 1 Banjarbaru. The method used in this research is a survey method. The population in this study was taken from male and female students at the State Senior High School 1 Banjarbaru aged 16-19 years, the population in the XI grade of the State Senior High School 1 Banjarbaru as many as 231 students. In comparison, the research sample was 184 students with the cluster sampling technique.The results of the research on the physical activity of students of SMA Negeri 1 Banjarbaru found that the classification of "low" was 84 students with a percentage of 45.65%. While the physical education learning outcomes of SMA Negeri 1 Banjarbaru students showed an average value of 82.11. The result of the calculation with the correlation shows 0.73 with the criteria of a strong/high relationship. Therefore, there is a relationship between physical activity and learning outcomes of PJOK students of SMAN 1 Banjarbaru. Physical education 85, high criteria as many as 21 people with an average score of 80.71 physical education. The criteria were as many as 71 people with an average score of 82.23 physical education. The low criteria were 84 people with an average score of 82.17 physical education and seven people with very low criteria with an average score of 85.57 physical education.